2019
DOI: 10.1001/jamanetworkopen.2019.18425
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of and Characteristics Associated With the Treatment of Calcium Channel Blocker–Induced Lower-Extremity Edema With Loop Diuretics

Abstract: IMPORTANCE Calcium channel blockers, specifically dihydropyridine calcium channel blockers (DH CCBs, eg, amlodipine), may cause lower-extremity edema. Anecdotal reports suggest this may result in a prescribing cascade, where DH CCB-induced edema is treated with loop diuretics. OBJECTIVE To assess the magnitude and characteristics of the DH CCB prescribing cascade. DESIGN, SETTING, AND PARTICIPANTS This cohort study used a prescription sequence symmetry analysis to assess loop diuretic initiation before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 61 publications
0
79
1
1
Order By: Relevance
“…Prescribing cascades are a contributor to problematic polypharmacy but are not captured within the numerous prescribing indicator sets aimed at reducing the use of inappropriate medications. Known prescribing cascades include those resulting from commonly used medications such as antihypertensives, NSAIDs and cholinesterase inhibitors 16,17,24,25 . Calcium channel blockers, particularly dihydropyridine calcium channel blockers, have been shown to result in a prescribing cascade whereby the resultant lower extremity oedema is treated with loop diuretics 16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribing cascades are a contributor to problematic polypharmacy but are not captured within the numerous prescribing indicator sets aimed at reducing the use of inappropriate medications. Known prescribing cascades include those resulting from commonly used medications such as antihypertensives, NSAIDs and cholinesterase inhibitors 16,17,24,25 . Calcium channel blockers, particularly dihydropyridine calcium channel blockers, have been shown to result in a prescribing cascade whereby the resultant lower extremity oedema is treated with loop diuretics 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Known prescribing cascades include those resulting from commonly used medications such as antihypertensives, NSAIDs and cholinesterase inhibitors 16,17,24,25 . Calcium channel blockers, particularly dihydropyridine calcium channel blockers, have been shown to result in a prescribing cascade whereby the resultant lower extremity oedema is treated with loop diuretics 16,17 . A dry cough is a common side effect of ACE inhibitors and has been shown to result in the prescription of a cough suppressant and antibiotics 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may become more severe during long-term therapy (Makani, Bangalore, Romero, Htyte, et al, 2011;Messerli, 2002). Faced with these edema, many pharmacoepidemiologic studies have shown that a very frequent therapeutic reflex consists in initiating diuretics (Savage et al, 2020;Vouri et al, 2019). Indeed, 2.3% of patients over 65 years of age newly treated with DHP experience this prescription cascade within one year of initiation (Vouri et al, 2019).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Faced with these edema, many pharmacoepidemiologic studies have shown that a very frequent therapeutic reflex consists in initiating diuretics (Savage et al, 2020;Vouri et al, 2019). Indeed, 2.3% of patients over 65 years of age newly treated with DHP experience this prescription cascade within one year of initiation (Vouri et al, 2019). Compared to renin angiotensin aldosterone system (RAAS) inhibitor prescription, this risk is significantly increased by 2.4 after a 3-month treatment (Savage et al, 2020).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%